PENERAPAN PENERAPAN GERAKAN LITERASI SEKOLAH SISWA KELAS XI SMK DARUSSALAM TORJUN TAHUN PELAJARAN 2023/2024: PENERAPAN GERAKAN LITERASI SEKOLAH SISWA KELAS XI SMK DARUSSALAM TORJUN TAHUN PELAJARAN 2023/2024 - Riskiyatul Laili; Ali Nurhadi; Tatik Maryana (Jurnal Cendekia Pendidikan, 2024)
The importance of literacy in the world of education as an effort to build a generation of people with broad insight and noble character. So the Government, through the Ministry of Education and Culture, issued Permendikbud no. 23 of 2015 concerning the Development of Characteristics (PBP) which is realized through the Implementation of the School Literacy Movement (GLS) from elementary to high school levels. Type study This is study descriptive qualitative. Subject study This is head school, students, and teacher at Darussalam Torjun Vocational School. Object study This at Darussalam Vocational School Torjun. Instrument in study This is writer as researcher. Technique collection data is carried out with technique interviews, observations And technique documentation. Data analysis was carried out with use Miles theory and Huberman with method data reduction , data display, and conclusion. From the research results it can be concluded that: (1) the implementation of the school literacy movement is carried out by implementing literacy activities in scheduled learning activities at each grade level and utilizing the role of the library. The implementation of GLS has gone well by looking at several literacy activities involving school residents in literacy (literacy teams). This literacy activity is still in the habituation stage. Students only read according to their interest and pleasure without being involved in assignments that are billing. (2) Difficulties in implementing the school literacy movement namely the lack of representative facilities and infrastructure, limited library books, and low interest in reading. (3) The solution to overcome difficulties in implementing the school literacy movement is that teachers provide rewards for students who are active and excel in literacy activities at school, so that apart from providing support for students they can also have confidence in expressing their imagination and other written works. Students bring their personal book collections and submit reading reports to increase students' literacy interest in the hope that students will not be lazy about reading.